2019
DOI: 10.1186/s12885-019-6202-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual oxidase 1 and NADPH oxidase 2 exert favorable effects in cervical cancer patients by activating immune response

Abstract: BackgroundNicotinamide adenine dinucleotide phosphate (NADPH) oxidase-derived reactive oxygen species (ROS) not only can promote cancer progression, but also they have recently emerged as mediators of the mucosal immune system. However, the roles and clinical relevance of the collective or individual NADPH oxidase (NOX) family genes in cervical cancer have not been studied.MethodsWe investigated the clinical significance of the NOX family genes using data from 307 patients with cervical cancer obtained from Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Interestingly, it has been previously reported that post-AKI rats had an increased expression of other pro-oxidant genes such as LPO, myeloperoxidase, and DUOX1 [51]. Moreover, gene set enrichment analyses in IRI condition revealed that high DUOX1 expression is significantly correlated with the enrichment of immune pathways related to interferon (IFN)-alpha, IFN-gamma, and natural killer (NK) cell signalling [52].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been previously reported that post-AKI rats had an increased expression of other pro-oxidant genes such as LPO, myeloperoxidase, and DUOX1 [51]. Moreover, gene set enrichment analyses in IRI condition revealed that high DUOX1 expression is significantly correlated with the enrichment of immune pathways related to interferon (IFN)-alpha, IFN-gamma, and natural killer (NK) cell signalling [52].…”
Section: Discussionmentioning
confidence: 99%
“…7D, 9C, 10I). Sang Yeon Cho et al Found that duox1 is highly expressed in cervical squamous cell carcinoma and can play a good prognostic role by increasing the amount of innate immune cells 54 . The analysis also showed that DUOX1 is highly expressed in tumor tissues and related to age and grade (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Although TOM1L1 regulates the oncoprotein ERBB2-driven cell invasion with metastatic phenotypes in breast cancer [ 33 ], there is no available information on the role of this gene in CC. Another gene predicting overall survival is DOXO1 (Dual oxidase 1), whose overexpression has been reported to promote favorable effects in CC patients via immune response activation [ 34 ]. In this study, we have observed that increased expression levels for this dual gene are related to a better prognostic.…”
Section: Discussionmentioning
confidence: 99%
“…Another gene detected in this study to be involved in CC pathogenesis is DUOX1. This gene plays a significant role in host mucosal immunity by producing hydrogen peroxide, thus serving as the first line of defense to HPV invasion, particularly in cervical cancer [ 34 ]. Yet another critical gene identified in this study is VEGF.…”
Section: Discussionmentioning
confidence: 99%